2020
DOI: 10.24843/matrik:jmbk.2020.v14.i02.p06
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepribadian Proaktif, Efikasi Diri dan Anticipatory Entrepreneurial Cognitions dalam Membentuk Niat Berwirausaha Mahasiswa

Abstract: Penelitian ini bertujuan untuk menguji bagaimana kepribadian proaktif dan kesadaran diri untuk berwirausaha dari mahasiswa dapat mempengaruhi niat berwirausaha pada mahasiswa yang dimediasi oleh efikasi diri kreatif, efikasi diri pembelajaran dan anticipatory entrepreneurial cognitions. Penelitian ini dilakukan pada mahasiswa Universitas Sebelas Maret, diambil dengan menggunakan teknik probability sampling yaitu proportional stratified random sampling dengan jumlah responden dalam penelitian ini sebanyak 610 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Thus, it can be concluded that the better the Anticipatory entrepreneurial cognitions felt by Respondents, the better Entrepreneurial Intentions will be. The results of this study are in line with the results of the study (Amanda et al, 2020) which shows that the variable Anticipatory entrepreneurial cognitions has a positive and significant effect on Entrepreneurial Intentions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, it can be concluded that the better the Anticipatory entrepreneurial cognitions felt by Respondents, the better Entrepreneurial Intentions will be. The results of this study are in line with the results of the study (Amanda et al, 2020) which shows that the variable Anticipatory entrepreneurial cognitions has a positive and significant effect on Entrepreneurial Intentions.…”
Section: Discussionsupporting
confidence: 90%
“…Anticipatory entrepreneurial cognitions cover a broad spectrum of thinking that is centered on discovering, exploring, and testing one's potential to become an entrepreneur. Individuals cognitively explore what it's like to be an entrepreneur in various ways such as testing assumptions, simulating various aspects of running a business, and trying to discover potential barriers to starting a business (Amanda et al, 2020). The results of this study are in line with the results of the study (Amanda et al, 2020) which shows that the selfefficacy variable has a positive and significant effect on Anticipatory entrepreneurial cognitions.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Time/effort. According to (Krishnan at Amanda et al, 2020) state that effort consists of varying amounts of time and energy a person spends in completing a task. A study by (Badri, 2020) showed that the ease of using services positively affects an attitude.…”
Section: Theoretical Reviewmentioning
confidence: 99%